Rates of planimetric change in a proglacial gravel‐bed braided river: Field measurement and physical modelling. Issue 3 (25th November 2018) - Middleton, L.; Ashmore, P.; Leduc, P.; Sjogren, D.
Abstract: Planimetric change was measured on daily hydrographs over two meltwater seasons using time‐lapse images of the proglacial, gravel, braided, Sunwapta River, Canada. Significant planimetric change occurred on 10–15 days per year. Area of planimetric change correlated with peak and total daily meltwater hydrograph discharge. A clear threshold discharge can be identified below which no planform activity occurs, an intermediate range over which change occurs conditionally, and a peak flow range at which significant change always occurs. Field conditions were reproduced in a physical model in a laboratory flume. Photogrammetric DEMs of bed morphology and measurements of bedload output were made for each hydrograph experimental run. The physical model results for planimetric change had a threshold discharge for change, and trend with discharge, similar to the field data. The model data also show that planimetric change correlates strongly with volumes of erosion/deposition measured from successive DEMs, and with bedload transport rate. The relation between planimetric change and topographic change is also apparent from previous cross‐section surveys at the field site. The results highlight the planimetric dynamics of braiding rivers in relation to discharge forcing, and the relationship between planimetric change, morphological change, and bedload transport in braided rivers. This also points to the potential use of measurements of planimetric change from time‐lapse imagery as a low‐cost method for high‐frequency monitoring for braiding dynamics and also a surrogate for bedload transport measurement. © 2018 John Wiley & Sons, Ltd. Abstract : Areas of planimetric change were measured in a proglacial, gravel‐bed, braided river and were found to increase in relation to peak and total daily meltwater discharge above a threshold. A physical model of the field site had similar planimetric change area and threshold discharge as the field data and showed that the threshold discharge for gravel bedload is almost the same as the planimetric change threshold. Morphological change and total bedload transport for a modelled hydrograph correlate with planimetric change.